L-carnitine versus Propranolol for pediatric migraine prophylaxis - Amini, Laya; Yaghini, Omid; Ghazavi, Mohammadreza; Aslani, Nahid (Iranian Journal of Child Neurology, 2021)
Objective Carnitine plays a significant role in fatty acid transportation in mitochondria and has been shown to have a prophylactic effect on adult migraine. The aim of this randomized controlled trial was to compare and evaluate the effects of L-carnitine supplementation versus propranolol in the prevention of pediatric migraine. Materials & Methods A total of 60 pediatric patients with episodic migraine were randomly allocated to 2 independent groups to receive either 50 mg/kg/day L-carnitine or 1 mg/kg/day propranolol as a prophylactic drug. Frequency, severity, and duration of migraine attacks and headache disability based on the Pediatric Migraine Disability Assessment Score (PedMIDAS) were studied at the baseline and after 2, 4, and 12 weeks. Results A total of 56 patients were evaluated in the study: 23 girls (41%) and 33 boys (59%) with a mean age of 9.7 ± 2.1 years. Frequency of migraine headaches per month reduced from 11.4 ± 7.1 to 5.34 ± 2.4 in the L-carnitine group and from 10.7 ± 6.2 to 4.96 ± 3.9 in the propranolol group by the end of the study. Headache severity score was also reduced from 19.38 ± 14 to 2.88 ± 7.4 and from 12.92 ± 13 to 0.82 ± 1.3 in the L-carnitine and propranolol groups, respectively. We found a significant decrease in frequency, severity, and duration of headache attacks in both groups (P < 0.01). No significant difference was observed between the efficacies of the 2 drugs. Conclusion This study concluded that L-carnitine supplementation can play a prophylactic role in the management of pediatric migraine.